The Olympic games explained : a student guide to the evolution of the modern Olympic games - Girginov, Vassil, 1956- (Student sport studies., 2005)
This new student textbook explores the history and meaning of the four-yearly phenomenon that is the modern Olympic Games. It provides a comprehensive overview of 'Olympism' from the Ancient Greeks origins through the beginnings of the International.